Existence of Unbounded Solutions for a Third-Order Boundary Value Problem on Infinite Intervals - Hairong Lian; Junfang Zhao (Discrete Dynamics in Nature and Society)
We generalize the unbounded upper and lower solution method to a third-order ordinary differential equation on the half line subject to the Sturm-Liouville boundary conditions. By using such techniques and the Schäuder fixed point theorem, some criteria are presented for the existence of solutions and positive ones to the problem discussed.